Macassan History and Heritage Journeys, Encounters and Influences - Clark, Marshall; May, Sally K. (ANU Press, 2013)
This book presents inter-disciplinary perspectives on the maritime journeys of the Macassan trepangers who sailed in fleets of wooden sailing vessels known as praus from the port city of Makassar in southern Sulawesi to the northern Australian coastline. These voyages date back to at least the 1700s and there is new evidence to suggest that the Macassan praus were visiting northern Australia even earlier. This book examines the Macassan journeys to and from Australia, their encounters with Indigenous communities in the north, as well as the ongoing social and cultural impact of these connections, both in Indonesia and Australia.